2013
DOI: 10.1088/0268-1242/28/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

Procedure to derive analytical models for microwave noise performances of Si/SiGe:C and InP/InGaAs heterojunction bipolar transistors

Abstract: We present a useful procedure to derive simplified expressions to model the minimum noise factor and the equivalent noise resistance of Si/SiGe:C and InP/InGaAs heterojunction bipolar transistors (HBTs). An acceptable agreement between models and measurements at operation frequencies up to 18 GHz and at several bias points is demonstrated. The development procedure includes all the significant microwave noise sources of the HBTs. These relations should be useful to model F min and R n for state-of-the-art IV-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For devices with equal Ge gradient (10-20%) but different N AB (B5-B7) the best F min performance is obtained by B5 (the component with the lowest N AB ) and as N AB increases F min degrades. This trend can be explained as follows: as described in [5] at f ≪ f T the static current gain (β) controls the F min amplitude, and as shown in table 2, β 5 > β 6 > β 7 . This β progression is consistent with the base doping level acting in two ways in the base-emitter junction efficiency.…”
Section: Apparent Base Resistance (R B ) Decompositionmentioning
confidence: 81%
See 1 more Smart Citation
“…For devices with equal Ge gradient (10-20%) but different N AB (B5-B7) the best F min performance is obtained by B5 (the component with the lowest N AB ) and as N AB increases F min degrades. This trend can be explained as follows: as described in [5] at f ≪ f T the static current gain (β) controls the F min amplitude, and as shown in table 2, β 5 > β 6 > β 7 . This β progression is consistent with the base doping level acting in two ways in the base-emitter junction efficiency.…”
Section: Apparent Base Resistance (R B ) Decompositionmentioning
confidence: 81%
“…These features will ensure the reliability of the extracted R Bi and R Bx values and that they are consistent with the HBT dynamic performances. The advantage of using MWN and S-parameters measurements to determine R Bx , X and R Bx relies on the fact that the base resistance distribution highly impacts the noise behaviour in bipolar devices [5].…”
Section: Introductionmentioning
confidence: 99%
“…This was expected because T2 has the highest static current gain; values are compared in table 2. Thus, T2 has the lowest NF min because the noise is inversely proportional to the current gain [29]. Furthermore, when we considered the modelling results for the two temperatures when C is taken into account, we found that at f=1 GHz NF min,300 K (J Copt )=1.3 dB, NF min,40 K (J Copt )=0.17 dB, (R n /Z 0 ) 300 K =1.48, and (R n /Z 0 ) 40 K =0.12.…”
Section: Static Hfn and Dynamic Performances Analysismentioning
confidence: 99%